KORELASI FUNGSI AFEKTIF KELUARGA DAN EFIKASI DIRI TERHADAP KEPATUHAN MINUM OBAT TUBERKULOSIS PARU : Studi Literatur - Erliana Mandasari (2020)
Pulmonary tuberculosis is a chronic infectious disease caused by mycobacterium mycobacterium tuberculosis and has become one of the world's problems that require long-term treatment for about 6 months or more to achieve healing, non adherence medication can cause drug resistance and even death. The hight adherence to taking anti-tuberculosis drugs can be influenced by family encouragement and good self-efficacy. The purpose of this study was to analyzed the correlation of family affective function and self-efficacy toward adherence to taking anti-tuberculosis drugs. The method was used a non-systematic literature review obtained by analyzed related journals to the research topic and in accordance with the inclusion criteria, a journal search strategy used internet sites that have been published from 2016 to 2020. The term used in literature search was "tuberculosis","family support","emotion of family","self efficacy"," medication adherence","drug compliance". The results showed based on 28 journals reviewed, found 25 journals showed a relationship of affective function and self-efficacy toward adherence to taking antituberculosis drugs. Research analysis related to Dorothy E. Johnson's theory. This conclusion shows the relationship between family's affective function and self-efficacy toward adherence to taking anti-tuberculosis medication.